Proteases as Therapeutic Targets Against the Parasitic Cnidarian Ceratonova shasta: Characterization of Molecules Key to Parasite Virulence In Salmonid Hosts - Alama-Bermejo, Gema; Bartošová-Sojková, Pavla; Atkinson, Stephen D.; Holzer, Astrid S.; Bartholomew, Jerri L. (Frontiers in Cellular and Infection Microbiology, 2022)
Proteases and their inhibitors play critical roles in host-parasite interactions and in the outcomes of infections. Ceratonova shasta is a myxozoan pathogen that causes enteronecrosis in economically important salmonids from the Pacific Northwest of North America. This cnidarian parasite has host-specific genotypes with varying virulence, making it a powerful system to decipher virulence mechanisms in myxozoans. Using C. shasta genome and transcriptome, we identified four proteases of different catalytic types: cathepsin D (aspartic), cathepsin L and Z-like (cysteine) and aminopeptidase-N (metallo); and a stefin (cysteine protease inhibitor), which implied involvement in virulence and hence represent target molecules for the development of therapeutic strategies. We characterized, annotated and modelled their 3D protein structure using bioinformatics and computational tools. We quantified their expression in C. shasta genotype 0 (low virulence, no mortality) and IIR (high virulence and mortality) in rainbow trout Oncorhynchus mykiss, to demonstrate that there are major differences between the genotypes during infection and parasite development. High proliferation of genotype IIR was associated with high expression of the cathepsin D and the stefin, likely correlated with high nutrient demands and to regulate cell metabolism, with upregulation preceding massive proliferation and systemic dispersion. In contrast, upregulation of the cathepsin L and Z-like cysteine proteases may have roles in host immune evasion in genotype 0 infections, which are associated with low proliferation, low inflammation and non-destructive development. In contrast to the other proteases, C. shasta aminopeptidase-N appears to have a prominent role in nematocyst formation in both genotypes, but only during sporogenesis. Homology searches of C. shasta proteases against other myxozoan transcriptomes revealed a high abundance of cathepsin L and aminopeptidase homologs suggesting common gene requirements across species. Our study identified molecules of potential therapeutic significance for aquaculture and serves as a baseline for future research aimed at functional characterisation of these targets.